Statistical modeling of energy production in biomass power plants in Brazil - Gomes, Henrique Costa; Garcia, Mario Vinicio; Conceição, Ana Paula Gatto da; Dória, Rita de Cássia Moreschi (Brazilian Journal of Production Engineering, 2026)
This study analyzed the installed capacity of biomass power plants in Brazil through a structured methodological approach. Initially, the data were preprocessed, including standardization of nomenclature, treatment of missing values, and creation of temporal variables. A descriptive analysis was carried out to characterize the distribution of capacity by biomass type and subtype, complemented by graphical visualizations such as evolutionary timelines, seasonal boxplots, and relative participation charts. Correlation analysis was applied to examine the relationship between the number of plants and the total installed capacity. Statistical tests included one-way ANOVA to verify significant differences among subtypes, followed by Tukey’s HSD post-hoc test for pairwise comparisons and calculation of the effect size (η²) to assess the practical relevance of the differences. The results revealed distinct patterns of installed capacity among biomass types, with sugarcane bagasse standing out, and also highlighted challenges such as seasonality and terminological inconsistencies. The integrated approach allowed the characterization of the national bioenergy landscape, providing insights for sectoral policies and future research on optimizing Brazil’s renewable energy matrix.